Simulation design of 542kWp DC/480kWp AC Solar Photovoltaic System at Institute of Southern Punjab - Muhammad Muneeb Khan; Sadiq Ahmad; Muhammad Usman Tariq; Zeshan Haider Anjum; Muhammad Amir Shafi (Sir Syed University Research Journal of Engineering and Technology)
Conventional methods of producing electricity are expensive, pollute the environment, need a lot of maintenance, and eventually run out of power. Because of this, it is imperative to take use of the unrealized potential of renewable energy sources that are also ecologically beneficial. At the Institute of Southern Punjab (ISP), Multan, Pakistan geographical location coordinates latitude 30° 17′ 20′′ N and longitude 71° 30′ 1′′ E. Current study developed an effective, long-lasting, and environmentally friendly Grid Tie PV System (GTPVS) to address this issue. One location where solar energy has enormous promise is Multan. At this location, the average yearly horizontal solar irradiance is 1861.8 kWh/m2/year and average diffuse horizontal solar irradiance 898.9 kWh/m2/year. In this study, PVSyst is used to calculate the performance ratio and various power losses, such as inverter, temperature-related losses, and losses from PV modules. Every day, 3026.26 kg of coal are saved, which is the same as growing 29062.87 Teak trees for life time. According to National Electric Power Regulation Authority (NEPRA) rule Tarif A3(66) is applied on universities and schools, where 60 Rs/kWh is unit cost in year 2024. The generated energy costs for Longi solar cell for proposed location in ISP Multan is 0.07 US dollars per kWh, while the standard energy pricing in Pakistan in 2024 is 0.21 US dollars per kWh. The simulation results show that, proposed RTSPVS design energy production is 966.4 MWh/year. Annual performance ratio (PR) for the proposed system is 85.8%.